(untitled) (The Batuk, 2021)
Following random effect GLS model, this study aims at examining the consequence of credit performance and capital adequacy of Nepalese commercial banks. For the analysis, the balanced panel data of 19 commercial banks have judgmentally been selected and used. The researcher took credit to deposit ratio (CDR), interest rate spread (IRS), non-performing loan ratio (NPLR) and capital adequacy ratio (CAR) as the predictors of profitability measured by return on assets (ROA) of the banks. The results indicate that the study predictors are significant in defining variation on ROA. The variables CDR and NPLR have significant negative impact on ROA. In contrast, the predictors IRS and CAR have positive consequence on ROA. However, the relationship between CAR and ROA is statistically insignificant. Results of the study can contribute as an important input to regulatory body in developing policy so as to make banking operation effective.